Functional divergence in oligopeptide transporters in plants - Kurt, Fırat; Filiz, E. (Elsevier, 2021)
OPTs (oligopeptide transporters) are integral membrane-localized proteins serving for the transport of various substrates in cells. OPT proteins are involved in the transport of tri-, tetra-, penta-, and hexapeptides and consisted of two subfamilies: yellow stripe or yellow stripe-like (YS or YSL) and peptide transport (PT) proteins. Substrate specificity of members of PT subfamily is tetra- and pentapeptides, relatively longer peptides (between 10 and 13 peptides), metals (iron, copper), GSH (Glutathione), GSH conjugates and complexes, and GSH-metal complexes (like Cd). On the other hand, YSL clade proteins are involved in metal acquisition (Fe, Zn, Mg, Mn, Cu), and in translocation of the metals in monocots and dicots through using chelators called phytosiderophores (PSs) (members of mugineic acids-MAs-) and nicotianamine (NA). Grasses use chelation mechanism in taking up iron and are called Strategy II plants. PSs are of importance uptake of metals from soil whereas NA is generally involved in long-transport of metals. The recent findings indicate that OPTs play critical roles in the regulation of responses to biotic and abiotic stresses. In this chapter, the functional roles of each subclass of OPT proteins are presented by including recent studies. © 2022 Elsevier Inc. All rights reserved.
Keywords: Heavy metals; Iron; Membrane transport; Mugienic acid; Nicotianamine; OPT; Peptide transport; Phytosiderophore; Transmembrane; YSL